The influence of different compositions of fiber metal laminates on the fracture in the semi-solidified stamping forming. (August 2022) - Li, Lei; Lang, Lihui; Hamza, Blala; Alexandrov, Sergei; Li, Shiyue
Fiber metal laminates (FMLs) are widely used in manufacturing due to the high specific strength, fatigue resistance, and lightweight. However, because of the deformation coordination of different layers of FMLs, challenges have been faced in rapid and small part forming. To research the feasibility of the fast forming of small parts using the FMLs, the influence of different compositions of FMLs on the stamping performance under the semi-solidified process condition was investigated, including the outer aluminum layer, the fiber lay-up direction in the middle layer, and the various states of the resin. Based on the results of Finite-element simulation and experiments, the semi-solidified process can improve the forming performance of FMLs by making the thickness distribution of the outer aluminum layers more uniform and preventing excessive fiber deformation. The coordination of fiber lay-up direction and interlayer forces can improve the forming limit height of semi-solidified FMLs. Besides, the fracture position of the cup part is related to the fiber lay-up direction and interfacial bonding performance in FMLs. This study provides necessary guidance for the rapid stamp forming of small parts using FMLs.